Manufacturing Technology of Sliding Bearings from Ferro-Graphite Compositions - Egorov, M. S.; Pustovoit, V. N.; Tsordanidi, G. G.; Egorova, R. V. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2022)
Introduction . The development of modern technology imposes increasingly stringent requirements on materials operating under conditions of high pressures, speeds, deformations and aggressive media. The use of powder metallurgy methods in the creation of new materials makes it possible to provide a rational combination of production technology, structural and performance characteristics. Powder steels used in mechanical engineering are of great interest among the materials obtained by powder metallurgy. The article explores the possibility of manufacturing porous bearings made of iron powder for fan motors of domestic air conditioners instead of porous bearings made of bronze graphite. Problem Statement . To ensure long-term operation of fan motors from metal powders, it is necessary to create porous bearings without alloying additives with the required mechanical properties. This requires a series of experimental work to determine the dependences of mechanical and technological properties on the sintering temperature, compacting pressure and the porosity of samples. Theoretical Part . As a theoretical description, the use of a mold with an additional draining gap, which provides high bearing density at low compacting pressure, is analyzed. The effect of compacting pressure on the strength of sliding bearings under mechanical deformations depending on the sintering temperature is also considered. Conclusions . It was established in the work that during the sintering of sliding bearings at a temperature of 800-1100°C, a significant charge carburization occurs due to the decomposition of zinc stearate in closed pores. As a result, a ferritepearlite structure is formed, due to which the bearings are well calibrated and have high wear resistance when paired with a steel shaft. Optimum sintering modes and compacting pressures were selected, which showed high reliability and durability of the products obtained from pure iron powder.